Architecture of Small Type Train Station in Yogyakarta, Indonesia - Masyiana Arifah Alfia Riza; Edy Darmawan; Ikaputra Ikaputra; Dimas Wihardyanto (Department of Architecture, Faculty of Engineering, Universitas Diponegoro, Indonesia., 2021)
The reason for the construction of the Ngabean (Yogyakarta)-Palbapang (Bantul)-Sewugalur (Kulon Progo) railway line with a length of 28 km was to accommodate 4 sugar factories along the line. In order to shorten the rail transport line on the Yogyakarta-Sewugalur railway line, 12 small stations were made. But unfortunately, in 1942 this line was closed causing some of these stations to be closed and disappeared. Among the available stations are Winongo Station, Bantul Station, and Palbapang Station. This study aims to look at the characteristics of 18th century Dutch Indonesian architecture in the station building. Knowing the architectural character of the station building can play as a reference for maintaining the conservation of historical buildings in Indonesia. This study employed a rationalistic-qualitative approach. To identify the architectural character of the station building, this study was conducted by looking at the spatial system, architectural system, and structural building system. From the results of the study, it was found that Winongo Station, Bantul Station, and Palbapang Station have a distinctive character both from the spatial system, architectural system, and structural system.